Opleiding in die nywerheid — ’n opvoedkundige taak? - Steyn, H. J. (Koers, 1983)
The author points out that low productivity is one of the causes of inflation in South Africa. He suggests that, apart from other factors, training is an important component in the. Achievement of improved productivity. Training in industry should therefore be seen as an important part of the whole system of non-formal education within the framework of education as such. He pleads for closer liaison between formal and non-formal education sectors. Training in industry in the non-formal sense should also be seen as part of the educative process, and be determined by a specific world view. He also looks at the personnel utilized in the training process, and he points out the various skills that the personnel should master for the most efficient attainment of the various objectives.